Challenges for Restoration of Coastal Marine Ecosystems in the Anthropocene - Abelson, Avigdor; Reed, Daniel C.; Edgar, Graham J.; Smith, Carter S.; Kendrick, Gary A.; Orth, Robert J.; Airoldi, Laura; Silliman, Brian; Beck, Michael W.; Krause, Gesche; Shashar, Nadav; Stambler, Noga; et al. (Frontiers in Marine Science, 2020)
Coastal marine ecosystems provide critical goods and services to humanity but many are experiencing rapid degradation. The need for effective restoration tools capable of promoting recovery of coastal ecosystems and remediating their valued services has never been greater. We identify four major challenges for the future development and implementation of coastal marine ecosystem restoration (MER): (1) Development of more effective, scalable restoration tools, (2) adaptation of restoration tools to cope with climate change and global stressors, (3) integration of social and ecological restoration priorities, and (4) promotion of the perception and use of coastal MER as a scientifically-credible management approach. Tackling these challenges should improve restoration success rates, heighten their recognition, and accelerate investment in and promotion of coastal MER. Here, to reverse the currently accelerating decline of marine ecosystems, we discuss potential directions for meeting these challenges by applying coastal MER tools that are science-based and actionable. For coastal restoration to have a global impact, it must incorporate social science, technological and conceptual advances, and plan for future climates.